Between Waqf and Inheritance: A Jurisprudential Analysis of Judicial Reasoning in Bantul Religious Court Decision No. 552/Pdt.G/2019/PA.Btl - Nur Muhamad Said Abdullah (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the intersection between waqf and inheritance within the framework of Islamic jurisprudence through an analysis of judicial reasoning in Bantul Religious Court Decision No. 552/Pdt.G/2019/PA.Btl. The dispute emerged from the legal ambiguity surrounding waqf land that remained formally registered under the heirs’ names without an official transfer of title to the nadzir, thereby triggering competing claims between inheritance rights and waqf status. This research aims to analyze how the court constructed its legal reasoning in resolving the tension between these two legal regimes. Employing a qualitative normative method with a juridical approach, the study relies on document analysis of the court decision and relevant legal materials, including statutory regulations and Islamic legal doctrines. The findings reveal that the court’s reasoning reflects a jurisprudential effort to reconcile normative Islamic principles with positive legal frameworks. The decision emphasizes the importance of formal legal administration in waqf management, particularly the obligation to transfer land certification to the nadzir to ensure legal certainty. At the same time, it demonstrates a balanced approach by safeguarding the proportional rights of heirs where procedural irregularities exist. This ruling contributes to the development of jurisprudence in Indonesia by offering a structured resolution model for waqf-related inheritance disputes and reinforcing the integration of Islamic legal principles within the national legal system.